KAJIAN ADSORPSI Zn(II) DENGAN MENGGUNAKAN LIMBAH JERUK (Citrus nobilis var. microcarpa) TERSAPONIFIKASI BENTUK Na DAN Ca - , PUJI KURNIAWATI; , Prof. Dr. Sri Juari Santosa, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The utilization of orange (citrus nobilis var. microcarpa) waste for the adsorption of Zn(II) has been examined in this study. The orange waste was modified through saponification using NaOH and Ca(OH)2 to form saponified orange waste of Na (SOW-Na) and saponified orange waste of Ca (SOW-Ca). The synthesis of SOW-Na and SOW-Ca was done by adding respectively the solutions of NaOH and Ca(OH)2 to the orange waste to achieve the solution medium pH 10, 10.5, 11, 11.5, 12 and 12.5. Characterization of SOW-Na and SOW-Ca was carried out using Fourier Transform Infrared Spectrophotometry (FTIR). The result showed that the highest ion exchange capacity of SOW-Na was achieved at pH 12.5, i.e. 1.53 mol/Kg, while SOW-Ca was at pH 11.5, i.e. 2.39 mol/Kg. Adsorption of Zn(II) on both SOW-Na and SOW-Ca was optimum at medium pH 6 and it followed pseudo second order with adsorption rate constant were 1.02Â·10-3 mM-1Â·min-1 and 2.40Â·10-3 mM-1Â·min-1, respectively. Adsorption of Zn(II) on both adsorbent fitted well to Langmuir isotherm with capacity 45.94 mg/g for SOW-Na and 41.06 mg/g for SOW-Ca. By using biner solution Zn(II) â Pb(II), the abilities of SOW-Na and SOW-Ca in adsorbing Zn(II) decreased significantly, while in biner solution Zn(II) â Cd(II) the abilities of the both adsorbents in adsorbing Zn(II) were affected insignificantly.